Sistem pengurusan makanan ringan (SPMR) (Rosly Masum SDN BHD) - Nur Syamimi Salma, Abdillah (2010)
Snack food industry is not less important in daily life. This is because many people involved in this field, especially the indigenous people. This industry is very lucrative returns. For example are food industry and rosly Azhar masum sdn bhd. although the industry is increasingly popular but the major problem in this industry in terms of management. Management in the industry takes it easy while many things have to be dealt with in the management of this industry. For example, food order, manage reservations, generate profit and soon. The very significant problem is during the festive season has received many orders. This project highlights the problems faced by Rosly Masum SDN BED is one of the companies involved in this field. Among the problems faced by Rosly Masum SDN BHD is the business done manually. Manual management has no security features to manage all information about customers and information about the products. This can cause all information is lost. In addition, to develop this system requires the allocation of Rosly Masum SDN BIRD. so , one way is needed to meet the requirement. The solutions proposed in the development of this system are to computerize the manual management and implement the document Software Development Plan (SDP), SRS (Software Requirement Specification) and the Software Design Document.